ECONOMIC-STATISTICAL ANALYSIS OF PROCESSING INDUSTRIAL ENTERPRISES - Baykuziyeva Gulsanam Adkhamovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article presents a system of statistical indicators that represent the structural activity of processing industrial enterprises and their economic and statistical analysis. Analysis of indicators of agricultural products aimed at processing enterprises, dynamics of indicators of production of processing enterprises and general agricultural products, analysis of organizational and economic indicators of some enterprises of the processing industry of the Fergana region has been carried out.